2023
DOI: 10.2174/1871530322666220630093359
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage in Type 2 Diabetes Mellitus: Macrophage Polarization a New Paradigm for Treatment of Type 2 Diabetes Mellitus

Abstract: Metabolic diseases such as type 2 diabetes mellitus are usually in association with meta-inflammation. β-cell failure is a marked feature observed in the pathogenesis of type 2 diabetes mellitus. Type 2 diabetes mellitus (T2DM) is a heterogeneous situation that is accompanied with not only defective insulin secretion but also peripheral insulin resistance. β-cells are the primary organ for insulin secretion hence, it is crucial to maintain a significant β-cell mass in response to a variety of changes. Insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…15,45,46 Recently, natural products have attracted scientists’ attention for their contribution to the limitation of macrophage inflammatory response in the intra-islets and pancreatic β-cell death to deliver the benefits for diabetes management. 44,47,48 In the present study, we first demonstrated that lycopene alleviates the disorders in glucose and lipid metabolism in HFD/STZ-induced diabetic mice. Secondly, lycopene treatment promotes the dynamic balance of M1/M2 macrophages in the islets of diabetic mice and in HG/PA-stimulated RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 54%
“…15,45,46 Recently, natural products have attracted scientists’ attention for their contribution to the limitation of macrophage inflammatory response in the intra-islets and pancreatic β-cell death to deliver the benefits for diabetes management. 44,47,48 In the present study, we first demonstrated that lycopene alleviates the disorders in glucose and lipid metabolism in HFD/STZ-induced diabetic mice. Secondly, lycopene treatment promotes the dynamic balance of M1/M2 macrophages in the islets of diabetic mice and in HG/PA-stimulated RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 54%
“…These types of investigations could provide a rationale for further testing of eMSC EXOs as a viable therapeutic modality to manufacture cell-free products for inflammatory conditions, including osteoarthritis and diabetes. Specifically, macrophage infiltration and pro-inflammatory activation has been associated with synovitis/fat pad fibrosis severity in the knee joints of osteoarthritis patients [ 40 , 41 ], as well as pancreatic islet viability/insulin secretion capacity in diabetes patients [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ZDF animals showed an increased number of macrophages primarily localized within the islets. Macrophages infiltrating diabetic islets express an M1-like pro-inflammatory phenotype, contributing to local overproduction of inflammatory cytokines and activation of the NF-κB signaling pathway, ultimately leading to beta-cell apoptosis and dysfunction [ 39 ]. Although metformin treatment did not reduce macrophage numbers, it did decrease their infiltration, thereby mitigating islet inflammation.…”
Section: Discussionmentioning
confidence: 99%